تصميم وإنجاز جهاز قياس درجة الحموضة لمتابعة المحاليل الكيميائية. - مروة, خلوط; شهرة, مرخي; بثينة, بابه (University of El-Oued, 2022)
"In many chemical, industrial, agricultural applications and studies, pH measurement is necessary. In this study, a design and implementation of pH measurement system for various chemical solutions based on the electrochemical method has been presented. The said method is characterized by flexibility and ease of exploitation of hardware and resources, in addition it provides high accuracy compared to the other methods. In order to design and implement the project, we presented a theoretical study of the various existing measurement methods. Then we carried out the design process, starting with selecting the hardware and the hard parts such as the Arduino Uno board, the pH sensor, the humidity and temperature sensor, and an LCD to show the measurement results. Then the necessary software for adapting the project to work on those pieces has been used. We simulated the proposed system first by Proteus ISIS, and tested it with various conditions to preview the results, improve the accuracy and efficiency. Based on simulation results, we implemented the proposed system in the laboratory using real hardware. Calibration of the system was carried out using prepared buffer solutions in laboratory. The obtained results showed a similarity with the simulation results with good accuracy. It showed also the possibility of using and exploiting the device in real applications." "في كثير من التطبيقات و الدراسات الكيميائية، الصناعية و الزراعية وغيرها يعتبر قياس الاس الهيدروجيني أمرا ضروريا. نسعى من خلال هذه الدراسة بالاعتماد على الطريقة الكهروكيميائية إلى تصميم وإنجاز جهاز قياس الـ pHلمختلف المحاليل الكيميائية. تمتاز هذه الطريقة بالمرونة و سهولة استغلال الادوات و الموارد كما توفر قياسات و دقة عالية بالمقارنة مع الطرق الاخرى. من أجل تصميم و انجاز المشروع قمنا في البداية بدراسة نظرية لمختلف طرق القياس الموجودة. ثم شرعنا بعملية التصميم انطلاقا من اختيار العتاد و القطع الصلبة كلوحة Arduino Uno و حساس الـpH و حساس الرطوبة و الحرارة و شاشة لإظهار نتائج القياس. ثم استعمال البرمجيات اللازمة لتكييف المشروع لتعمل على تلك القطع. اجرينا عملية محاكاة للجهاز المقترح بواسطة برنامجProteus وتعريضه لمختلف الظروف لمعاينة النتائج و تحسين الدقة و الفعالية. و على ذلك الأساس تم إنجاز المشروع باستعمال القطع الحقيقية في المخبر. ثم قمنا بمعايرة النظام باستخدام محاليل منظمة حُضرت مخبريًا. وقد أظهرت النتائج المحصل عليها وجود تطابق مع نتائج المحاكاة بدقة مقبولة وأظهرت امكانية استعمال و استغلال الجهاز في التطبيقات الحقيقية."
مذكرة ماستر تخصص هندسة طرائق
Keywords: pH meter, pH, Arduino, Proteus, Buffer solution, sensor.; جهاز قياس الـpH، الأس الهيدروجيني، أردوينو، Proteus، محاليل منظمة، حساس.